Understanding Emergency Dental Health Literacy Among Indonesian Migrants in Singapore: A Cross?Sectional Survey - Frida Arba Martadewi; Erma Sofiani; Dita Sri Erisona; Salma Nabita Eldurr; Fahma Aldihyah Kunsputri (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Dental health literacy is crucial in managing emergency dental and oral health issues, especially for Indonesian migrant workers in Singapore who have limited access to healthcare services. The Singapore Department of Statistics reported that as of 2023, there were 1.77 million non-residents in Singapore, a 13.1% rise from the year before. This growth was mostly due to foreign employment in domestic and construction-related industries. Language barriers, economic constraints, and differences in healthcare systems contribute to a low understanding of emergency dental actions. This study aims to analyze this group’s emergency dental health literacy level. Methods: This study employed a descriptive cross-sectional quantitative design using a survey method on 124 Indonesian migrant workers in Singapore. Data was collected through a Likert-scale-based questionnaire to measure participants' understanding, attitudes, and self-efficacy in handling emergency dental situations. Data analysis was conducted using descriptive analysis, reliability testing, Spearman’s correlation, and the Kruskal-Wallis comparative test. The study has received ethical approval from the Ethics Committee of the Faculty of Medicine and Health Sciences at Universitas Muhammadiyah Yogyakarta (FKIK UMY), and participants provided informed consent in order to protect participants' rights. Results: The Cronbach’s Alpha reliability test produced a value of 0.803, indicating good internal consistency. A total of 76.6% of respondents understood emergency dental management steps, while 92% recognized the importance of seeking medical assistance if a toothache persisted for more than two days. However, only 57.3% were aware of safe over-the-counter medications for dental pain relief. Education played a role in improving dental health literacy, but no significant differences were found based on age. Conclusion: The majority of Indonesian migrant workers in Singapore have a relatively good understanding of emergency dental health literacy; however, improvements are needed in the selection of appropriate medications. This study highlights the need for more effective awareness programs and policy support to enhance access to dental health information, enabling migrant workers to handle emergency dental issues appropriately. Concrete interventions such as increasing emergency dental literacy can be done with mobile dental health outreach, multilingual training programs, and connecting with networks in the migrant community.